Monitoring and controlling sand and dust storms in the Middle East - Al-Dousari Ali; Elrawy Mohammed (E3S Web of Conferences)
Satellite images from May 1968 to March 2023 identified two major hotspots (source areas) for sand and dust storms (SDS) in southern Iraq. Around 40 million people in the region are momently affected by the SDS hotspots in Kuwait, southern Iraq, southern Iran, Qatar, eastern Saudi Arabia, Emirates, Bahrain, and northern parts of Oman. The two SDS hotspots cause approximately 40% of the total SDS in the region (SDS data from 1993-2023). The two SDS hotspots are shrinking with time by 85.5% in 2023 (3 373 km2) compared to 23, 331 km2 in 1984. A rehabilitation project (2023-2026) between Iraq and Kuwait Institute for Scientific Research (KISR) funded by UN-Habitat and Kuwait Fund for Arab Economic Development (KF) uses mechanical and biological fixation for SDS hotspots. Both SDS intensity and counts were reduced during 2023 in most of the Arabian Gulf countries compared to the years 2012 to 2021.